ORGANIC RICE BUSINESS MODEL ANALYSIS USING CANVAS BUSINESS MODEL APPROACH: ANALISIS MODEL BISNIS BERAS ORGANIK DENGAN MENGGUNAKAN PENDEKATAN MODEL BISNIS KANVAS - Edi Paryanto; Rizki Puspita Dewanti; Hardian Ningsih; Rysca Indreswari; Ana Agustina (Yayasan Education and Social Center, 2021)
The population of Indonesia is very large, which is 270.2 million people and the level of public awareness in consuming organic rice is getting higher, so it can be said to be a pretty good business prospect. This is an attraction to conduct a deeper and broader study of the organic rice business model that can be developed. The organic rice business at this time has not been widely seen by most farmers, this is due to the lack of knowledge of farmers in managing organic rice businesses and still lack of support from supporting institutions in developing this organic rice business. Therefore, there needs to be a special study of the organic rice business model which hopes to be a reference to the knowledge, replication and development of organic rice businesses of farmers in the future. The problems that will be examined are as follows: 1) How the existing organic rice business model, 2) How the capacity of the organic rice business in generating existing profits, 3) How the new organic rice business model is based on the results of the company's SWOT review at this time. Therefore the specific purpose of the research to be implemented is 1) Identifying existing organic rice business models using canvas business model approaches, 2) Identifying organic rice business capacity in generating profits using potter value chain approach, 3) Creating a new organic rice business model using canvas business model approach. This research approach used is qualitative descriptive research with case study methods. The research site was conducted at the Appoli Boyolali cooperative. The types of data needed are primary data and skunder with data collection techniques are document studies, in-depth interviews, questionnaires, and observations. Data sources come from documents, objects, events and sources / informants. Resource /informant selection technique by purposive sampling and snowball sampling. The data analysis technique in this study uses descriptive analysis techniques, namely by describing the nine elements of the Business Model Canvas, evaluation using SWOTs analysis as well as Porter value chain analysis. Based on the research that has been carried out obtained the following conclusions 1) the organic rice business model that now exists is quite good but still needs to be refined again. Some of the disadvantages are customer segments that have not been clearly defined, value propositions that have not been adequately branded, how to build relationships that have not been holistic, key activities that are not complete, governments that have not been intensively involved, and revenue streams that have not varied. 2) Business capacity measured based on porter value chain also shows that business capacity in generating margin still needs to be increased again. Both the main and supporting activities still need to be improved even though they cannot be done in a short period of time, 3). The new organic rice business model needs to be developed by APPOLI cooperatives by adding and correcting activities in the old business model with several strategies with reference to the utilization of the power they have to achieve existing opportunities.